Unlocking Teacher Creativity: How Organizational Support Sparks Innovative Work Behavior - Abdul Rahman; Sriwiyani Sriwiyani (Tarbawi: Jurnal Keilmuan Manajemen Pendidikan, 2025)
This study aims to examine and analyze the influence of organizational support on teacher creativity and innovative work behavior, with organizational support as a mediating variable, at MAN 2 Nganjuk. This research employs a quantitative approach. Considering the research problems and objectives, an explanatory research design with a survey approach was used. The questionnaire was developed based on the study variables: organizational support, teacher creativity, and innovative work behavior. Data were collected from 100 teachers who served as the study sample, selected through random sampling at MAN 2 Nganjuk. Data analysis was conducted using the Partial Least Squares (PLS) method in SmartPLS. The study's results indicate that organizational support significantly influences teacher creativity and innovative work behavior. Good organizational support, such as facilities, leadership attention, and recognition, can increase teacher motivation to innovate and develop creativity in learning. Innovative work behavior significantly influences teacher creativity. Organizational support also significantly influences teacher creativity through innovative work behavior. The implications of this research confirm that organizational support plays a crucial role in enhancing teacher creativity when managed through targeted, innovative work behavior. Educational institutions need to provide facilities, policies, and a collaborative work environment that values teachers' ideas and innovation while maintaining a balanced workload.